Eternal Bibliotheca : Library as a multigallery / Faculty of Art & Design, UiTM Puncak Alam - Junaidi, Afiq (Faculty of Art & Design, Universiti Teknologi MARA, 2019)
Library is actually where all the input and output are produced. All the knowledge that people need have in a library whether for children, teenagers, college students, adults or senior citizen. Unfortunately, nowadays there are no more people like to go to the library.